Bimbingan Teknis Problematika dan Tata Kelola Usaha Koperasi Wilayah Binaan Dinas Koperasi dan UMKM Kabupaten Demak - Hardiningsih, Pancawati; Mariana, Novita; Srimindarti, Ceacilia; Sulastri , Sulastri (Universitas katolik Musi Charitas, 2021)
The failure of a business carried out by novice entrepreneurs occurs because they set up a business without thinking. This happens because the preparation is not yet mature, so that it develops its business on the fly and many adjustments must be made during the course of the business because from the start the business model is not right. This happened to MSME players and cooperatives under the guidance of the Department of Cooperatives and UMKM in Demak Regency. The canvas business model is an alternative design using a business model, it will be easier to get business certainty, it is easy to see the current state of the business and how to advance it. This business model can also be used as a basis for creating a business plan. Guidance is carried out as a form of understanding the introduction of a strategy to read business conditions and potential, governance and growth up zone of internal and external potential for good and structured management of MSMEs and cooperatives for business actors. The result of this training activity is that cooperative managers and SME entrepreneurs have the knowledge, insight and are able to make a business model that fits the business plan.